(untitled) (Socio-economic relations in the digital society, 2019)
The analysis of influence on the economy of Ukraine of financial and credit strategy of activity of the banking system, analyzed the possible consequences of the use of strategy of investment activity, which makes basis of activity of the banking system of islam type. A conclusion is got, that Ukraine, as the state, has prospects on existence only on condition of reorientation of bank activity from a credit in an investment, taking advantage of experience of the banking system of islam type.